A Comprehensive Literature Review of Diagnosis and Management of Multi Drug Resistant Tuberculosis - Erick Persson Jeffry; Charles Sanjaya Seikka (The Indonesian Journal of General Medicine, 2025)
Background: The review of the literature on the diagnosis and management of multidrug-resistant tuberculosis (MDR-TB) reveals a pressing global health challenge characterized by complex factors influencing its prevalence and treatment. (Chhabra et al., 2012) lay the groundwork by identifying systemic issues such as inadequate healthcare resources and poor case detection as significant contributors to the MDR-TB epidemic.  Literature Review: (J. Sloan & M. Lewis, 2016) further contribute to the discourse by exploring novel treatments and their applicability in low-resource environments. They emphasize the importance of improved diagnostics and the integration of new therapeutic strategies, while also addressing the financial barriers associated with MDR-TB treatment. (Kolloli & Subbian, 2017) shift the focus to host-directed therapies, arguing for innovative management strategies to address the complexities introduced by co-infections and chronic illnesses. They call for a reevaluation of traditional treatment regimens, particularly for patients with MDR- and extensively drug-resistant tuberculosis (XDR-TB), highlighting the need for approaches that enhance effectiveness. (Yadav, 2023) reviews recent advancements in MDR-TB research, particularly in diagnostic technologies and treatment methodologies. The article reinforces the urgency of addressing the global challenge posed by MDR-TB through innovative strategies that facilitate faster and more accurate diagnosis, ultimately aiming for improved patient outcomes. Conclusion: In conclusion, the literature collectively illustrates the dynamic and intricate landscape of MDR-TB management. The articles underscore the critical need for continued research, enhanced diagnostics, and innovative treatment strategies to effectively combat this growing public health crisis. A multifaceted approach that includes international collaboration, financial investment, and the integration of new technologies is essential for addressing the challenges posed by MDR-TB and improving patient outcomes.